1994
DOI: 10.1021/bi00172a024
|View full text |Cite
|
Sign up to set email alerts
|

Internal Electron Transfer in Cytochrome c Oxidase Is Coupled to the Protonation of a Group Close to the Bimetallic Site

Abstract: Absorbance changes following CO dissociation by flash photolysis from mixed-valence cytochrome oxidase have been followed in the Soret and alpha regions. Apart from CO dissociation and recombination, three kinetic phases with rate constants in the range 10(5)-10(3) s-1 at pH 7.5 can be resolved in both spectral regions. The slowest one of these phases, which had earlier only been observed in the alpha region, has now been detected in the Soret region by the use of a low CO concentration to slow down the recomb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

13
62
0

Year Published

1996
1996
2007
2007

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 77 publications
(75 citation statements)
references
References 36 publications
(37 reference statements)
13
62
0
Order By: Relevance
“…As found previously (15,18,19), the extent (absorption change amplitude) and rate of the ms-phase electron-transfer reaction were both strongly pH dependent. In addition, we have shown here that changes in conductance take place with the same time constant as the absorbance changes associated with electron transfer between cytochrome a3 and a.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…As found previously (15,18,19), the extent (absorption change amplitude) and rate of the ms-phase electron-transfer reaction were both strongly pH dependent. In addition, we have shown here that changes in conductance take place with the same time constant as the absorbance changes associated with electron transfer between cytochrome a3 and a.…”
Section: Discussionsupporting
confidence: 83%
“…These reactions are followed by a slower electron equilibration in which additional electrons are transferred from cytochrome a3 to a on a millisecond time scale (this reaction will be referred to as the ms phase), presumably limited by the proton release. As found both in the bovine (15,19) and Rhodobacter sphaeroides bacterial enzymes (18), both the extent and time constant of this reaction are pH dependent; the time constant increases from about 0.5 ms at pH 6 to about 6 ms at pH 10 and more electrons are transferred at high pH than at low pH (15,18,19). This behavior was modeled in terms of electrostatic interactions between the binuclear center and a protonatable group in the vicinity of cytochrome a3 (18,19), in contact with the bulk protons through a proton-conducting pathway, which limits the proton-exchange rate with the bulk and, as a consequence, also the rate of the ms-phase electron transfer from cytochrome a3 to a (19).…”
supporting
confidence: 65%
See 1 more Smart Citation
“…This reaction was originally reported to consist of two phases (5,6): a Ϸ3-s phase of eT between the heme groups was followed by slower electron equilibration with an additional copper site (Cu A ) that lies at the membrane interface in some of the heme-copper oxidases but that is lacking in others (7,8). More recently, it was shown that a third phase of interheme eT (50 s to milliseconds) that is coupled to proton release from the binuclear center can be observed after CO photolysis at high pH (9)(10)(11). However, with the quinol-oxidizing cytochrome bo 3 from Escherichia coli, even more phases were discerned (12).…”
mentioning
confidence: 99%
“…10 and 11, there are two separate input channels in COX for the uptake of ''pumped'' and ''chemical'' protons. Evidence for electrogenic movement of protons within the channel involved in the protonation of the binuclear center from the mitochondrial matrix was reported (12,13) and ionization of groups within this channel is apparently coupled to electron transfer between hemes a and a 3 (14,15).…”
mentioning
confidence: 99%